Refletores automotivos fabricados com policarbonato contendo dióxido de titânio - Isabella Luísa Vieira Aquino Cassimiro (2019)
Polycarbonate (PC) associated with Acrylonitrile - Butadiene- Styrene (ABS) is the most widely used material for the manufacture of automotive vehicle's internal lantern reflectors. However, the resulting polymer has no reflective properties and must undergo a metallization process. It is interesting to develop alternative polymers for the manufacture of reflectors that do not require the metallization phase. According to the literature, the use of titanium dioxide ( TiO 2 ) associated with ceramic or polymeric materials, promotes improvement in the optical properties of these materials. In this sense, this research investigates the performance of reflectors manufactured with ABS-associated polycarbonate and TiO 2- added polycarbonate . After characterization of the materials, weld resistance tests, reflective efficiency, accelerated aging test and infrared thermography are performed. The weld resistance, the luminous efficiency, the durability and the thermal performance of the components are evaluated. The results indicate that the reflector made of polycarbonate and TiO 2 addition has lower illuminance than metallized but remains within the acceptable range of reflection required in the automotive industry. It is observed that welding the lens with the body of the flashlight does not compromise it’s resistance or appearance. Accelerated aging shows that both parts perform similarity. When subjected to the heat generated by the lamps, the TiO 2 flashlight is 11 ̊C below the temperature measured on the metallized flashlight. These results indicate polycarbonate with the addition of Titanium Dioxide as a potential substitute for the metallization phase of automotive vehicle interior lanterns.